Prenatal caffeine exposure caused H‐type blood vessel‐related long bone dysplasia via miR375/CTGF signaling. Issue 2 (18th March 2021) - He, Hangyuan; Luo, Hanwen; Liu, Liang; Shangguan, Yangfan; Xie, Xingkui; Wen, Yinxian; Wang, Hui; Chen, Liaobin
Abstract: Caffeine has developmental toxicity. Prenatal caffeine exposure (PCE) caused intrauterine growth retardation (IUGR) and multiple organ dysplasia. This study intended to explore the effect and mechanism of PCE on long bone development in female fetal rats. In vivo, the PCE group pregnant rats were given different concentrations of caffeine during the gestational Day 9‐20. The mRNA expression of osteogenesis‐related genes were significantly reduced in PCE group. In the PCE group (120 mg/kg·d), the length and primary center of fetal femur were shorter, and accompanied by H‐type blood vessel abundance reducing. Meanwhile, connective tissue growth factor (CTGF) expression decreased in the growth plate of the PCE group (120 mg/kg·d). In contrast, the miR375 expression increased. In vitro, caffeine decreased CTGF and increased miR375 expression in fetal growth plate chondrocytes. After co‐culture with caffeine‐treated chondrocytes, the tube formation ability for the H‐type endothelial cells was decreased. Furthermore, CTGF overexpression or miR375 inhibitor reversed caffeine‐induced reduction of tube formation ability, and miR375 inhibitor reversed caffeine‐induced CTGF expression inhibition. In summary, PCE decreased the expression of CTGF by miR375, ultimately resulting in H‐type blood vessel‐related long bone dysplasia.